Analisis Kesesuaian Wisata dan Kesediaan untuk Membayar Kategori Wisata Rekreasi di Pantai Samuh, Bali - Arief, Angel Maria; Pertami, Nyoman Dati; Pratiwi, Made Ayu (Journal of Marine and Aquatic Sciences; Vol 8 No 2 (2022), 2022)
This study aimed to determine the tourism suitability index and the willingness to pay (WTP) for the category of beach recreation tourism in Samuh Beach area, Bali. The research method used was descriptive qualitative. The parameters used to determine the value of the coastal recreation were beach type, beach width, current speed, brightness, depth, beach slope, water base material, current velocity, coastal land cover, hazardous biota, and availability of fresh water. The calculation result of the tourism suitability index value at Samuh Beach for beach recreation activities at station I was 2.05% which included in the Suitable category, station II was 2.88% which included in the Very Suitable category, and Station III was 2.92% which included in the category. Very Suitable category. Based on that result, it can be seen that station III occupies the highest IKW value in the Very Suitable category. The average value of tourism suitability index in Samuh Beach was 2.62% (very suitable category). The average value of the WTP was IDR 9.500,- and the total value was IDR 57.000.000,- - at Samuh Beach. This value was greater than the entrance fee for Samuh Beach tourism in the form of a motorbike parking fee of IDR 2000, - and a car park of IDR 5000,- respectively. Respondents are willing to pay more for environmental services obtained from tourism objects in Samuh Beach.